(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The closed shell of neutrons or protons means there is no boson numbers, which are important for applying IBM models. The properties of nuclear structure for isotopes depend on the boson numbers. If they are small the vibrational properties will appear or nearby from these properties. our theoretical results using two models (IBM-1 and IBM-2) are acceptable matching regard to the energy levels with the experimental data, electric transitions and potential energy surface. For neutron number 82,84Kr is nearby 50 closed shell which has transition properties between U(5) and O(6), 132,134Xe is nearby 80 has U(5) properties and nearby 126 but for 202,204Hg have different properties.